Averting the old age crisis : policies to protect the old and promote growth - World Bank. (Oxford ; New York : Published for the World Bank [by] Oxford University Press, 1994)
This policy-oriented study identifies the issues that individual countries should consider as they re-evaluate their current income security policies and formulate new methods. The basic conclusion is that a mixed strategy is more effective than any single method of income security
Includes bibliographical references
Keywords: Old age pensions; Retirement income; Older people -- Economic conditions; Old age assistance; Economic security